MODIFIKASI AGAR-AGAR DENGAN UBI JALAR UNGU DAN SUBSTITUSI PEMANIS ALAMI DAUN STEVIA - Kun Harismah; Linda Fatmawati; Ismaae Yusoh; Choirul Huda Septianto; Denny Vitasari; Aan Sofyan; Ahmad Muhammad Fuadi (Universitas Muhammadiyah Semarang, 2015)
The present study has been conducted to formulate novel pudding based using a mixture of agar (Gracilaria sp), purple sweet potato (Ipomoea batatas) and cinnamon aroma by replacing sucrose partly with stevia. Five different treatments of purple sweet potato agar were prepared with sucrose/Stevia ratios of 100:0, 25:50, 50:50, 25:75, and 0:100. All the products were evaluated by sensory evaluators. Test results showed that organoleptic test by taste, aroma, texture, and color of the highest value obtained on variations sweet potato agar with a concentration of stevia 50 % (sucrose and stevia 1:1).Keywords: Agar, cinnamon, purple sweet potato, stevia